The Influence of Self Leadership and Psychological Empowerment on Mediated Performance by Job Satisfaction Lecturers of Private Universities in Yogyakarta - Muhamad Ali Sukrajap; FX. Wahyu Widiantoro (AIBPM Publisher, 2018)
Joint Regulation of the Minister of Education and Culture No. 4 / VII / PB / 2014 and Head of State Civil Service Agency No. 24 of 2014 concerning Lecturers' Functional Position and Credit Numbers states that Lecturer Academic Position is a position that shows the duties, responsibilities, authority and rights of a Lecturer in a higher education whose implementation is based on certain expertise and is independent. Based on this, lecturers are required to develop their knowledge independently in the sense that lecturers must be able to direct or lead themselves to be able to improve their performance as lecturers, on the other hand that lecturers also need to give freedom in carrying out their duties and responsibilities in the “Tri Dharma” college. The number of lecturers in the 2016/2017 school year was 237,837 people with the number of distribution based on functional positions as professors as many as 4,949 people (2.1%), Head of Lectors as many as 29,287 people (12.3%), Lectors as many as 46,620 people (19.6% ), Expert Assistant as many as 47,871 people (20.1%) and No Position as many as 109,110 people (45.9%). The highest composition based on the percentage of ownership of academic positions is Lecturer without Academic Position. This study aims to determine the effect of Self Leadership with Psychological Empowerment on Performance mediated by Job Satisfaction Lecturers of Private Higher Education Foundation in Yogyakarta. This research was carried out in 9 universities in Yogjakarta with a total of 74 participating as permanent lecturers at private universities in Yogyakarta. Analysis of research data using simple regression analysis and multiple regression analysis. This study shows that all the hypotheses proposed in this study are acceptable. Other things also show that there is an imperfect mediation effect in this study, where the comparison of the regression coefficients of independent and dependent variables is smaller if compared with the regression coefficient when regression of the independent variable and mediator on the dependent variable. This indicates that there are other variables other than job satisfaction that have an influence on the self leadership relationship, psychological empowerment and performance that have not been studied in this study. Keywords: Self Leadership, Psychological Empowerment, Job Satisfaction, Performance